ASEAN as a Subject of International Law: Its Role in the Formation of International Treaties - Haneefa, Adzka (Universitas Sebelas Maret, 2022)
ASEAN or the Association of Southeast Asian Nations is one of the international organizations that involves several countries, namely countries in the Southeast Asian region. International organizations in International Law act as a very important subject to make and regulate a law and rules to its member countries, ASEAN is certainly a subject of International Law as an organization that regulates and makes agreements in accordance with mutual agreement. Agreements made by ASEAN apply to more than one country, so they are international agreements. It is important to outline ASEAN's role in making international agreements over the years. International treaties address agreements, rules that then bind countries that have agreed to the treaty. Such treaties can be categorized as sources of International Law. One example of an agreement that ASEAN has made to its member states is when the ASEAN Charter was signed at the 13th ASEAN Summit on November 20, 2007 by each head of State or government of ASEAN member states. There is an agreement regarding the reaffirmation of the basic principles of the formation of ASEAN. So this is where the role of ASEAN then acts as a maker of agreements aimed at common welfare.